Sequence Stratigraphic Analysis Within The Zambezi Depression, Offshore Northern Mozambique Basin - Benjamim Samuel, Carlitos (Bulletin of Earth Sciences of Thailand, 2021)
The post-rift sequence stratigraphy within the Zambezi Depression is significantly controlled by relative sea level, sediment supply and subsidence rate. The Knowledge of basinal stratigraphic architecture and basin evolution is very useful for the exploration of oil and natural gas resources. Ten regional stratigraphic surfaces and associated depositional sequences were interpreted in the study area. Depositional pattern, were analyzed to evaluate the variable influences of relative sea level and sediment supply rate on depositional processes. The depositional sequences were categorized into three main magasequences based on sea level changes and sediment supply. Sediment supply changed through geological time, initially sediments were supplied from the SW and SE, in the later stage sediment supply was from the west. Considering the factors affecting different depositional processes, basin evolution can be divided into three phases. Phase 1: consists of non-marine deposits probably controlled by slope gradients. Phase 2: deposits were mainly controlled by systematic transgressive and regressive cycles and this stage is comprised of shallow to deep marine sediments suggesting a basin floor fan. Phase 3 is the youngest and consists of progradational clinoforms indicating that sediment supply outpaces the accommodation space. The prospectivity for hydrocarbon is high in sequences which and dominated by turbidities and are associated with canyon infill and basin floor fans.